Early outcomes after cochlear implantation for adults and children with unilateral hearing loss. (12th October 2016) - Sladen, Douglas P.; Carlson, Matthew L.; Dowling, Brittany P.; Olund, Amy P.; Teece, Kathryn; DeJong, Melissa D.; Breneman, Alyce; Peterson, Ann; Beatty, Charles W.; Neff, Brian A.; Driscoll, Colin L.
Abstract : Objectives/Hypothesis: This study was designed to examine speech recognition and self‐perceived health‐related quality of life (HRQoL) received from cochlear implantation among a cohort of adults and children with a short duration of unilateral hearing loss greater than 6 months, but less than 2 years. Study Design: Single‐subject repeated measures prospective study. Methods: This study assessed changes in speech recognition and self‐perceived quality of life by prospectively analyzing data at the preoperative evaluation and at the 3‐month and 6‐month postactivation intervals. Measurement tools included Medical Outcomes Study Questionnaire Short Form 36, Nijmegen Cochlear Implant Questionnaire, Speech Spatial and Qualities of Hearing–Comparative, and speech recognition measures in quiet and in noise. Results: Results indicated significant improvement in speech recognition, both in quiet and noise. Quality‐of‐life measures showed a significant increase in self‐perceived benefit with disease‐specific instruments, but remained constant with a generic HRQoL instrument. Conclusions: Cochlear implantation was a successful intervention for improved hearing in quiet and noise, and a self‐perceived benefit for this group of adults and children with a short duration of unilateral hearing loss. Level of Evidence: 4 Laryngoscope, 127:1683–1688, 2017